2020
DOI: 10.1007/s10856-020-06455-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial activity and compressive strength of a dental cement modified using plant extract mixture

Abstract: Literature lacks sufficient data regarding addition of natural antibacterial agents to glass ionomer cement (GICs). Hence, the aim of the study was to increase the antimicrobial properties of GICs through its modification with mixture of plant extracts to be evaluated along with an 0.5% chlorohexidine-modified GIC (CHX-GIC) with regard to biological and compressive strength properties. Conventional GIC (freeze-dried version) and CHX were used. Alcoholic extract of Salvadora persica, Olea europaea, and Ficus ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
(53 reference statements)
2
16
0
Order By: Relevance
“…GIC modified with S. persica , F. carcia, and O. eoropaea extract mixtures has shown significant antimicrobial activity against S. mutans before, which is the main causative organism of dental caries and M. luteus , which is a sensitive marker to the release of antimicrobial agents [ 28 ]; thus, this study aimed to assess two important clinical properties of GIC, which are shear bond strength and film thickness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GIC modified with S. persica , F. carcia, and O. eoropaea extract mixtures has shown significant antimicrobial activity against S. mutans before, which is the main causative organism of dental caries and M. luteus , which is a sensitive marker to the release of antimicrobial agents [ 28 ]; thus, this study aimed to assess two important clinical properties of GIC, which are shear bond strength and film thickness.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the CHX-GIC group showed statistically significant lower median values compared to all the plant-modified groups (1:2, 1:1, 2:1). The reason for this could be due to the presence of Cinnamic and bornyl acetic carboxylic acids in the plant extract mixture [ 28 ]. According to Prentice et al [41, those carboxylic acids might have been existed in a considerable amount that improved release of ions from the surface of the glass ionomer powder through lowering the pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the plant extracts enhanced the antimicrobial activity, especially against S. mutans . Meanwhile, the compressive strength was improved by the addition of the plant extracts in higher concentrations [ 51 ]. The inhibitory effect of S. persica on the collagen degradation of a demineralized dentin lesion was also studied.…”
Section: Dental Applications Of Salvadora Persicamentioning
confidence: 99%
“…Examples of materials that could be added to the powder of a plain cement are a quorum-sensing inhibitor drug[ 113 ], Ti-doped ZnO[ 114 ], nano-GO nanosheets[ 115 ], selenium nanoparticles[ 116 ], Ag-nanoparticle-reduced GO nanocomposite[ 117 ], chitosan hybrid nanoparticles[ 118 ], a Cu cluster molecule[ 119 ], powder prepared from extract from a Tunisian lichen[ 120 ], Yb-doped ZnO nanoparticles[ 121 ], and an analog of PKZ18 (PKZ18-22), a molecule that has been shown to block growth of antibiotic-resistant S. aureus in biofilm[ 122 ]. Examples of materials that could be added to the liquid of a plain cement are benzothiazole or one of its derivatives[ 123 , 124 ] and a natural antimicrobial agent (such as extract of Salvadora persica , Olea europaea , and Ficus carcia leaves[ 125 ] or biosynthesized ZnO nanoflowers[ 126 ]).…”
Section: Future Prospectsmentioning
confidence: 99%